Plus a Life Sentence? Incarceration’s Effects on Expected Lifetime Wage Growth - Theodore S. Corwin III; Daniel K.N. Johnson (Research in Applied Economics, 2024)
The United States incarcerates citizens at rates higher than those of any other developed nation, with impacts on not only government budgets but economic growth rates. Using the National Longitudinal Survey of Youth for 1997, we model the effects of incarceration on wage growth rates using inverse probability weighted regression adjusted (IPWRA) propensity score matching to recognize the selection bias among the members of the sample who serve prison terms. Results show that incarceration reduces average lifetime income growth by one-third even for a relatively short earning period, with that depth depending on length of sentence, employment history, and education level in some surprising ways.